2017
DOI: 10.17135/jdhs.2017.17.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Study on Clinical Dental Hygiene in Korea Based on Analysis of Clinical Dental Hygiene Curriculum of Fones School in the United States

Abstract: The aim of this study was to analyze in depth the standardized Clinical dental hygiene curriculum of the Fones School in the United States. We investigated the clinical dental hygiene curriculum in 2015∼2016 including title, credit, hours, contents, goals, competencies, and evaluation. We obtained the course syllabus and data related to each subject, for each grade, from the professors and students at the university. The goals and competencies, of the clinical dental hygiene program, which were based on the go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Dental Nutrition and Oral Biochemistry can be approached as an integrated curriculum because the learning contents are linked and overlapped. In the United States, they are already being integrated and operated as a subject called 'Nutritional Biochemistry' 12) . Also, in this study, when the educational contents were identified as keywords in each textbook of Dental Nutrition and Oral Biochemistry, it was confirmed that a number of keywords (approximately 30%) were overlapped (results not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental Nutrition and Oral Biochemistry can be approached as an integrated curriculum because the learning contents are linked and overlapped. In the United States, they are already being integrated and operated as a subject called 'Nutritional Biochemistry' 12) . Also, in this study, when the educational contents were identified as keywords in each textbook of Dental Nutrition and Oral Biochemistry, it was confirmed that a number of keywords (approximately 30%) were overlapped (results not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Because Oral Biochemistry deals with the types of substances constituting the human body and oral cavity, their chemical properties, roles, and metabolic processes, there is a link between the knowledge covered in Dental Nutrition and Oral Biochemistry 10) . Also, looking at the curriculum of Fones School (Bridgeport, CT, USA), Dental Nutrition and Oral Biochemistry are being integrated into the subjects of 'Nutritional Biochemistry' 12) . Touger-Decker 13) said that as the evidence proving the role of nutrition on the health and disease of the body and oral cavity is increasing, it is necessary to expand the operation by integrating nutrition with other basic or clinical subjects in medical and dental education.…”
Section: Introductionmentioning
confidence: 99%
“…In other academic fields in the health and medical field, evaluation institutes are being operated to manage the quality of education in order to strengthen competency. Therefore, dental hygiene educational institutions and research institutes should actively improve various educational programs and evaluation methods [15] using cutting-edge educational media to acquire practical and professional skills for strengthening dental hygiene competency.…”
Section: Discussionmentioning
confidence: 99%
“…This subject presents the standard 'core' competencies and other competencies, e.g. for health promotion, disease prevention, and the application of Dental Hygienics management, to allow the students to accomplish expertise and quality outcomes as dental hygienists necessary in clinics (Choi et al, 2017). Thus, the Clinical Dental Hygienics units of study should involve processes that cause the students to comprehensively think and make judgments using the concepts explored in prerequisite subjects.…”
Section: Design Of Subjects As Pbl Units Of Studymentioning
confidence: 99%